Reducing the consumption of personal protective equipment by setting up a multifunctional sampling station in the emergency department to screen for COVID-19 infection in Taiwan - Po-Ting Lin; Ting-Yuan Ni; Tren-Yi Chen; Chih-Pei Su; Hsiao-Fen Sun; Mu-Kuan Chen; Chu-Chung Chou; Po-Yu Wang; Yan-Ren Lin (Komiyama Printing Co. Ltd, 2020)
Abstract In Taiwan, high-risk patients have been identified and tested for preventing community spread of COVID-19. Most sample collection was performed in emergency departments (EDs). Traditional sample collection requires substantial personal protective equipment (PPE), healthcare professionals, sanitation workers, and isolation space. To solve this problem, we established a multifunctional sample collection station (MSCS) for COVID-19 testing in front of our ED. The station is composed of a thick and clear acrylic board (2 cm), which completely separates the patient and medical personnel. Three pairs of gloves (length, 45 cm) are attached and fixed on the outside wall of the MSCS. The gloves are used to conduct sampling of throat/nasal swabs, sputum, and blood from patients. The gap between the board and the building is only 0.2 cm (sealed with silicone sealant). ED personnel communicate with patients using a small two-way broadcast system. Medical waste is put in specific trashcans installed in the table outside the MSCS. With full physical protection, the personnel conducting the sampling procedure need to wear only their N95 mask and gloves. After we activated the station, our PPE, sampling time, and sanitization resources were considerably conserved during the 4-week observation period. The MSCS obviously saved time and PPE. It elevated the efficiency and capacity of the ED for handling potential community infections of COVID-19.